2003
DOI: 10.1021/jf026172s
|View full text |Cite
|
Sign up to set email alerts
|

Maillard Reaction Products Inhibit Oxidation of Human Low-Density Lipoproteins in Vitro

Abstract: Dietary intake of antioxidants has been associated with a reduced risk of cardiovascular diseases, which is very likely caused by their capability of prevent oxidation of low-density lipoproteins (LDL). During food processing and storage, substances with antioxidative properties are formed by Maillard reactions. In this study, the activity of Maillard products to inhibit copper-induced oxidation of human LDL in vitro was investigated. d-Glucose was heated with an equimolar amount of glycine, l-lysine, or l-arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 30 publications
0
57
0
1
Order By: Relevance
“…Lingnert (1980) described that addition of MRPs derived from histidine and glucose to cookie dough successfully inhibited the oxidation of lipids in cookies. Dittrich et al (2003) for the first time demonstrated clearly that Maillard reaction products derived from D-glucose and amino acids can prevent oxidation of human low-density lipoprotein in vitro. For the pathway of antioxidant activity of MRPs, a lot of studies have been done on the mechanism, but it is still not very clear due to the complexity of MRPs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lingnert (1980) described that addition of MRPs derived from histidine and glucose to cookie dough successfully inhibited the oxidation of lipids in cookies. Dittrich et al (2003) for the first time demonstrated clearly that Maillard reaction products derived from D-glucose and amino acids can prevent oxidation of human low-density lipoprotein in vitro. For the pathway of antioxidant activity of MRPs, a lot of studies have been done on the mechanism, but it is still not very clear due to the complexity of MRPs.…”
Section: Introductionmentioning
confidence: 94%
“…The mouthfulness characteristic, therefore, is considered to be associated with molecular weight (MW) distribution of products. On the other hand, it has been reported that MRPs are associated with strong antioxidant activity (Yen and Hsieh 1995;Yoshimura et al 1997), such as scavenging DPPH radicals in model glucose-lysine system (Morales and Jiménez-Pérez 2001), chelating ferrous ion (Yoshimura et al 1997), copper ion (Dittrich et al 2003) and scavenging peroxyl radical in glucose-glycine system (Wagner et al 2002), reducing power and lipid peroxidation inhibiting activity in casein-glucose system (Gu et al 2009). Lingnert (1980) described that addition of MRPs derived from histidine and glucose to cookie dough successfully inhibited the oxidation of lipids in cookies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Maillard reaction products (MRPs) were also thought to be related to the increased antioxidant activity of ginseng by heat processing, 5,6) because the Maillard reaction has been thought to be the major source correlated with increased efficacy by heat processing in various crude drugs or foods. 12,13) On the other hand, ginsenoside is one of the easily changeable components of ginseng by heat processing, 2,14) but heat processing-induced chemical and activity changes of ginsenosides considering the Maillard reaction have not yet been fully elucidated. In addition, the contents of less-polar ginsenosides Rg 3 , Rk 1 , Rg 5 , and maltol are known to increase by heat processing, and these compounds are supposed to be produced by the deglycosylation of diol-type ginsenosides and the Maillard reaction in ginseng by steaming.…”
mentioning
confidence: 99%
“…Their identity has not been established yet, but they may represent products of Maillard reactions [10]. Such continuous supply of antioxidants could offer indeed an effective antioxidative barrier, especially in the case of FCJ, for which the increase of the antioxidative potential during heat treatment occurs to a higher degree [29][30][31]. Another means enabling the detection of oxidative processes applied in this study was a spectrophotometric followup of the reaction of double bond conjugation upon oxidation in UV light.…”
Section: Resultsmentioning
confidence: 99%